APPROACHES INFLUENCING THE SELF-DEVELOPMENT OF STUDENTS IN THE CREDIT-MODULAR SYSTEM - Kholmatov Shokirjon Solievich (Journals Park Publishing, 2023)
In this article, we consider the functional, systematizing and subject-targeted approaches that affect the development of the individual during self-study of students on a credit-modular system. At the same time, we will also focus on the pedagogical foundations of the process of self-study on a credit-modular system.
Keywords: Credit-modular system, self-study, functional approach, subjective-target approach, systematizing approach.